De herinrichting van het kerkinterieur. Verslag van een literatuuronderzoek - Rompay-Daniëls, Monique Van (Jaarboek voor liturgieonderzoek, 1996)
After the Second Vatican Council changes of the interior of old churches have become a subject of constant concern. This article draws attention to the issue starting from experiences in Germany and Austria. Usually we are dealing with churches that were built in the last century in a neo-style. Most of the data were collected from the periodicals Das Münster and Kunst und Kirche. First I give some comment about the notion of space as the place where the liturgy is performed. Secondly a few cases of changes in the interior are dealt with, which show, because of their variety, that there are no ready-made solutions for a redesign of a church. Finally I give attention to the present state of affairs in the redesigning of churches. What is the role of the architect, what is the position of the different bodies and authorities involved, and which role can the community play? My hope is that this survey will be useful as a frame of reference in the discussions about the renewal of the interior of churches in the Netherlands.